2006
DOI: 10.1097/01.qai.0000224974.67962.ce
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Associations Between Mitochondrial DNA Levels and Current Treatment Status in HIV-Infected Individuals

Abstract: Current NRTI exposure is the major determinant of tissue mtDNA, but the precise determinants are tissue specific. Both ddI and d4T exposure are associated with fat mtDNA depletion, whereas ddI exposure was the only observed association with mtDNA depletion in PBMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…In a recent study with adults, d4T and ddI use was associated with fat mtDNA depletion, whereas ddI exposure was the only observed association with mtDNA depletion in PBMCs (10).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study with adults, d4T and ddI use was associated with fat mtDNA depletion, whereas ddI exposure was the only observed association with mtDNA depletion in PBMCs (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, most published studies, as well as the results in this current study, indicate that mtDNA levels in PBMCs perform poorly in identifying mitochondrial toxicity in fat. 13,[15][16][17][18][39][40][41] This may be due in part to the difficulty in purifying PBMCs consistently without platelet contamination. Platelets have mitochondria (and mtDNA) but lack nuclei and variable platelet contamination may result in erratic mtDNA:nDNA ratio measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, while mtDNA levels have been consistently demonstrated to be depleted in adipose tissue of lipoatrophic subjects, 7,[12][13][14] mtDNA levels in peripheral blood mononuclear cells (PBMCs) do not correlate well with either clinical lipoatrophy or with mtDNA levels in fat. 13,[15][16][17][18] Mitochondrial protein levels, and in particular levels of enzyme complexes of the oxidative phosphorylation system (OXPHOS), may be more informative indicators of mitochondrial function than are measurements of mtDNA. The mitochondrial OXPHOS system is essential for energy metabolism and normally provides more than 95% of ATP used for cellular energy.…”
mentioning
confidence: 99%
“…Decreased mitochondrial DNA (mtDNA) content has been described in adipose tissue from patients receiving NRTI treatment (15)(16)(17) and in vitro studies have demonstrated specific NRTI toxicity (18). In addition, in vivo tissue-selective toxicity has been reported (19,20) and polymerase gamma polymorphism may modify toxicity (13).…”
mentioning
confidence: 97%
“…Changes in mtDNA in peripheral blood cells can precede blood lactate increase (31) and d4T and ddI molecules, in particular, showed a stronger association with blood lactate increase (32). However, tissue-selective toxicity yielded contradictory results between blood and specific tissues more susceptible to damage, such as muscle or adipose tissues (19). Spermatozoa are clinical materials that are easily obtained without invasive procedures and could be useful biological markers of the adverse effects of HAART (33), due to sperm mitochondrial sensitivity (23,24).…”
mentioning
confidence: 97%